Some conditions for cyclic chief factors of finite groups - Gao, B.; Miao, L.; Tang, J. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
A subgroup $H$ of a finite group $G$ is called $\scrM$ -supplemented in $G$ if there exists a subgroup $B$ of $G$ such that $G = HB$and $H_1B$ is a proper subgroup of $G$ for every maximal subgroup $H_1$ of $H$. The main purpose of the paper is to study theinfluence of $\scrM$ -supplemented subgroups on the cyclic chief factors of finite groups.